2008
DOI: 10.1182/blood-2008-01-132787
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow microenvironment controls the in vivo differentiation of murine dendritic cells into osteoclasts

Abstract: IntroductionAn increasing number of studies underline the interactions between the bone and immune systems and have led to the emergence of osteoimmunology. 1,2 Excessive bone resorption is frequently associated with chronic infections and autoimmune and inflammatory diseases. [3][4][5][6] The immune system plays a major role in this process, in particular through activated T cells, which secrete proinflammatory cytokines involved in osteoclastogenesis. 7 However, less is known about the involvement of other i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
109
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(125 citation statements)
references
References 53 publications
12
109
0
3
Order By: Relevance
“…(14) Others have shown that RANKL and M-CSF are highly expressed in the BM of oc/oc mice. (20) By qRT-PCR we confirmed this but also saw a normalization of the expression levels of these important cytokines in the BM of oc/oc mice 18 to 20 days after transplantation (Fig. 5A, B).…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…(14) Others have shown that RANKL and M-CSF are highly expressed in the BM of oc/oc mice. (20) By qRT-PCR we confirmed this but also saw a normalization of the expression levels of these important cytokines in the BM of oc/oc mice 18 to 20 days after transplantation (Fig. 5A, B).…”
Section: Resultssupporting
confidence: 67%
“…Previously, oc/oc mice have been transplanted without prior conditioning with dendritic cells, but only a partial reversal of osteopetrosis and short prolongation of the lifespan were seen. (20) In another recent study, oc/oc mice were injected every 3 days with in vitro-derived osteoclast progenitors and a low number of c-kit þ bone marrow cells. (23) This leads to only a few weeks of increased survival despite the repeated administration of cells.…”
Section: Discussionmentioning
confidence: 99%
“…This increase in osteoclast numbers in vivo is most likely a compensatory response to the increased bone density or decreased resorption capacity of the osteoclasts, and because of the higher expression of Rankl and Csf1 (M-CSF) in þ/R740S bones, (10) consistent with what is seen in oc/oc mice. (27) In contrast, we show that in vitro osteoclastogenesis is impaired, resulting in smaller and fewer osteoclasts in þ/R740S cells compared with þ/þ cells, a phenomenon not observed in the other murine models. In addition, we found that the presence of both a wild-type and an R740S a3 protein, which does not detectably alter expression levels or targeting of the a3 protein to appropriate cellular sites, impairs lysosomal proton pumping and acidification (Fig.…”
Section: Discussionmentioning
confidence: 41%
“…[8][9][10] (Figure 2). Une étude récente vient de démontrer que l'injection de DC purifiées de la rate pouvait partiellement restaurer le phénotype ostéopétrotique de souris oc/oc dépourvues d'ostéo-clastes [11]. Ces résultats mettent donc en évidence l'existence d'un nouveau précurseur ostéoclastique tardif, au même titre que les monocytes et les macrophages.…”
Section: Origines Diverses Des Précurseurs Ostéoclastiquesunclassified